Educational Boost Slashes SIDS Risk Awareness Gap Among Nurses in Iraq: Peningkatan Pendidikan Memangkas Kesenjangan Kesadaran Risiko SIDS di Kalangan Perawat di Irak - Safa Ahmed Mohammed; Afifa Radha Aziz (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the impact of an educational program on nurses' knowledge of Sudden Infant Death Syndrome (SIDS) risk factors at pediatric teaching hospitals in Baghdad City. Using a quasi-experimental design with fifty nurses divided into a control and a research group, we assessed knowledge levels through pre-tests and two post-tests. Results indicated that the educational intervention significantly improved nurses' knowledge from 60% to 76%, although this effect diminished slightly over time. The study underscores the importance of continuous education in enhancing nurse awareness and the implementation of safe sleep practices to reduce SIDS occurrences. Highlights: Educational Impact: The study demonstrates a significant increase in nurses' knowledge about SIDS risk factors following an educational intervention. Sustained Learning: Knowledge gains were observed to diminish slightly over time, highlighting the need for ongoing educational programs. Practical Implications: Enhanced nurse training supports safer sleep practices, potentially reducing the incidence of SIDS. Keywords: Nurse Education, Knowledge, Risk Factors, Sudden Infant Death Syndrome, Safe Sleep Practices